Anatomical landmark-guided laparoscopy for migrant fishbone - induced pancreatic abscesses: a case series study and review of the literature - Chuanbing Zhao; Chuanbing Zhao; Hongzhen Wei; Hongzhen Wei; Long He; Long He; Canglong Deng; Canglong Deng; Yu Lu; Yu Lu; Jingjie Wang; Jingjie Wang; et al. (Frontiers in Medicine)
IntroductionPancreatic abscesses resulting from gastrointestinal fishbone migration represent rare yet clinically challenging surgical emergencies, with standardized management protocols remaining undefined.MethodsWe analyzed three consecutive cases (2024–2025) treated via anatomical landmark-guided laparoscopy alongside 11 PubMed-indexed cases (2004–2025). This study evaluates a novel surgical paradigm for complete foreign body retrieval and abscess resolution.ResultsThe laparoscopic strategy achieved technical precision with minimal operative duration (73 ± 6 min) and blood loss (6.67 ± 4.71 mL), eliminating pancreatic fistula or hemorrhagic complications. Postoperative hospitalization was reduced by 43% compared to conventional interventions (5.3 ± 1.5 vs. 9.3 ± 3.1 days; *p* < 0.01). Crucially, this strategy attained hemostatic efficacy equivalent to augmented reality navigation (ARN)-assisted techniques without preoperative conditioning.ConclusionThese findings establish a reproducible framework integrating anatomical landmark navigation for emergency pancreatic abscess management. The approach offers clinically validated advantages in procedural safety, visceral preservation, and accelerated recovery trajectories compared to existing strategies.